Role of Molecular Targeted Therapeutic Drugs in Treatment of Glioblastoma: A Review Article - Singh, Himanshu (Global Medical Genetics, 2023)
Glioblastoma is remarkably periodic primary brain tumor, characterizing an eminently heterogeneous pattern of neoplasms that are utmost destructive and threatening cancers.An enhanced and upgraded knowledge of the various molecular pathways that cause malignant changes in glioblastoma has resulted in advancement of numerous biomarkers and the interpretation of various agents that pointedly target tumor cells and microenvironment. In this review, literature or information on various targeted therapy for glioblastoma is discussed. English language articles were scrutinized in plentiful directory or databases like PubMed, ScienceDirect, Web of Sciences, Google Scholar, and Scopus. The important keywords used for searching databases are “Glioblastoma,” “Targeted therapy in glioblastoma,” “Therapeutic drugs in glioblastoma,” and “Molecular targets in glioblastoma.”
Keywords: glioblastoma; targeted therapy; molecular targets; therapeutic drugs